Choral singing as social practice: a study on institutions and amateur singers in Portugal - Lima, M. J. (13th Conference of the European Sociological Association, 2017)
The practice of choral singing has a significant expression in Portugal revealed by hundreds of groups identified and characterized by this research. These groups mobilize around choral singing practice thousands of individuals, from singers to composers, conductors, ethnographers, among others. In recent years, new media technologies also contribute to increase the dynamism of this practice. Following an epistemological, theoretical and methodological proposal that focus the ‘modes of relating to culture’, this paper explores the social relations that are established between the individuals (the singers) and the institutions (the choirs). Articulating quantitative and qualitative methodologies from an extensive survey on amateur choirs and from fieldwork research including individual interviews to amateur singers), this paper explores the institutional context of the amateur choral practice in Portugal, presents the typologies of choral groups through the multivariate analysis of the data and explores the motivations, constraints and impacts of choral practice in the everyday life.